TRADISI HAUL DALAM PERSPEKTIF AHLUSUNNAH WAL JAMAAH: KAJIAN LITERATUR TERHADAP DIMENSI KEAGAMAAN DAN SOSIAL - Sindy Intan Nadila; Miladia Nurul Aulia; Nurul Mubin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The haul tradition is a widely practiced religius custom among Muslim communities, particulary within the Ahlusunnah Wal Jamaah circle. This article aims to explore haul as a tradition encompassing both religious and social dimensions, as well as to examine scholarly prespectivies on its implementation. This study employs a qualitative approach using library research methods and content analysis techniques, focusing on various relevant sources, including clasiccal texts, contemporary fatwas, and academic literature. The finding that indicate that within the Ahlusunnah Wal Jamaah framework, haul is generally accepted as long as i tis carried out with sincere intentions and does not contradict Islamic principles. Furthermore, haul functions as a medium for da’wah, social solidarity, and the cultivation of moderate Islamic values. Despite differing opinions on its legitimacy and practice, haul continues to hold a significant role in preserving both the spiritual and social heritage of Muslim community.